MEMBANGUN ILMU-ILMU SOSIAL PROFETIK PERSPEKTIF KUNTOWIJOYO - Syahrul Nizar Saragih (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This paper discusses Kuntowijoyo's thoughts on "Islamic science". As for the method used descriptive analysis. The results are that Kuntowijoyo wants Muslims to change their way of thinking in seeing reality, from a mythical approach to an Islamic approach. it is here need Islamic scientific process which is expected birth of prophetic social sciences. As for the steps is to place Islam as a text, then analyzed through an analytic approach. Furthermore, the essence of Islamic teachings is examined through the approach of integralization and objectification to produce prophetic social sciences.